Socio-demographic determinants of intimate partner violence in Angola: a cross-sectional study of nationally representative survey data - Skandro Simona; Abio Anne; Baernighausen Till; Wilson Michael L (SPRINGER WIEN, 2025)
Intimate Partner Violence (IPV) is a global problem of public health importance, which can be found across all social layers and cultural backgrounds worldwide. Angola is still an under-explored country in the context of domestic violence and was therefore chosen as our focus of interest. Our study's goal was to identify the socio-demographic determinants of IPV in Angola. We used nationally representative data from female respondents of the 2015 Angolan Demographic and Health Surveys (DHS). Simple bivariate and multiple logistic regression analyses were used to assess the relationship between the experience of IPV and the women's' individual and contextual characteristics. Out of the 7,699 respondents, 3,070 (41.1%) reported having experienced at least one form of violence by their partners, with physical violence being more prevalent (32.5%) than emotional (27.7%) and sexual violence (7.2%). The partner's use of alcohol, the respondent's tendency to hurt her partner, her having witnessed her father beating her mother and being the first wife showed significantly higher odds of experiencing one or more types of IPV, whereas being older than the partner appears to have protective effects. Our findings reflect the widespread prevalence rates of violence against women in African countries. Future intervention programs should focus on women with risky background characteristics to help decrease domestic abuse in Angola. Our results indicate to focus on young women who have witnessed domestic violence in childhood, those whose partners use alcohol and those who tend to physically hurt their partners themselves. It is also recommended to intensify future research on the effects of co-wives on a relationship since first wives were found to have a higher risk of being physically abused by their partners.